Properties of new polycationic bacteriochlorin photosensitizers: cytotoxicity and interaction with biofilms - Irina Tiganova; Yulia Zhizhimova; Eteri Tolordava; Elena Makarova; Natalia Shevlyagina; Alexander Barmashov; Maria Baryshnikova; Vladimir Zhukhovitsky; Yulia Romanova (Exploration of Drug Science)
Aim: Biofilms of pathogenic bacteria are phenotypically resistant to antibiotics and other antimicrobial agents, host immune systems, and adverse environmental conditions, and are responsible for most chronic infections. Antimicrobial photodynamic therapy (APDT) is based on using of photosensitizers (PS), which generate reactive oxygen species when exposed to visible or infrared light. Previously, we demonstrated the high efficacy of new polycationic bacteriochlorins as PS against biofilms of Gram-negative bacteria Pseudomonas aeruginosa in vitro. Now, we compared the toxicity of these PS to bacteria and human fibroblasts, under irradiation and in the dark. Another goal was to study the interaction of the PS with the biofilm matrix without irradiation. Methods: Photodynamic inactivation of eucaryotic cells was obtained with MTT test, and with plating of planktonic bacteria P. aeruginosa and biofilms after disrupting. The interaction of PS with the matrix was studied with electron microscopy, alcian blue staining, and quantitative evaluation of polysaccharides. Results: The absence of dark toxicity of polycationic bacteriochlorins BCl-6 and BCl-7 for human fibroblasts WI-38 at concentrations up to 200 µM and the selectivity of the studied PS to P. aeruginosa 32 bacteria, including these in biofilms, under irradiation, were found. After incubation of P. aeruginosa 32 biofilms with tetracationic BCl-6 and BCl-5 without irradiation, gross disturbances in the structure of the biofilm matrix were observed by SEM, as well as a significant reduction of Alcian blue staining and polysaccharides in the matrix. Conclusions: Polycationic bacteriochlorins BCl-6 and BCl-7 had no dark toxicity for human fibroblasts and were selective to P. aeruginosa 32 bacteria, including these in biofilms, under irradiation. The incubation of biofilms of Gram-negative bacteria with polycationic bacteriochlorin led to the destruction of the matrix without irradiation.